Características clínico-epidemiológicas en relación a reacciones adversas en pacientes con tratamiento targa mayor de 5 años en el Hospital Regional de Loreto - Sevillano Zárate, Jhonatan Alejandro (2025)
Introduction: The Human Immunodeficiency Virus is one of the most reported viral infectious pathologies in the world. It continues to be one of the biggest problems for the world in terms of public health, it has already claimed around 30 million lives since it was first detected, mainly due to opportunistic infections that coexist with this infection. Since the first case of AIDS was discovered in Peru in 1983 and until 2024, more than 177,000 cases have been reported, of which more than 49,000 are in the AIDS stage. The last 20 years have seen an increase in HIV cases, but AIDS cases appear to be on a more stable course, possibly due to the addition of new medications and treatment options, this probably due to the addition of new drugs and treatment regimens, in addition to prevention programs and groups that constantly promote this pathology. Objective: Identify clinical-epidemiological characteristics in relation to adverse reactions in patients with ART treatment over 5 years at the Loreto regional hospital. Method: Observational, descriptive and cross-sectional study with selected patients from the ART program of the Loreto Regional Hospital. Through a census, all patients who complied with active ART treatment with a duration greater than or equal to 5 years and who were over 18 years of age and under 50 years of age were included. Results: A total of 540 medical records were reviewed, 294 were excluded for presenting exclusion criteria, therefore 246 medical records of patients with more than 5 years on ART treatment with ages between 18 and 50 who met the inclusion criteria at the Loreto Regional Hospital were selected. The most commonly used pharmacological therapy was the combination of Tenofovir disoproxil fumarate – Lamivudine – Dolutegravir in 78.5% of cases. 97.2% of patients received different prior ART treatment at the time of data collection. Most of them are male (63.8%), with an average age of 35.13 years, most of them in the range of 40 to 45 years (24%), it should be noted that the data obtained were not adjusted. They come from the Iquitos district (48.4%) and around 92.3% of the patients are from the province of Maynas. Adverse reactions in our study population occurred 43.9% of the time and among them the one that occurred most frequently was gastrointestinal symptoms, which included nausea, vomiting or diarrhea, occurring in 21.1% of the entire population. Adverse reactions to ART treatment are considered mild in 79%. Patients who presented some comorbidity at some point during ART treatment were 34.1%. Pulmonary tuberculosis was present in 12.6% of the patients included in the study, but represents 36.9% of the reported comorbidities. The variables of age, sex, origin and previous ART treatment were not statistically significant (p-value>0.05). On the other hand, the choice of therapeutic scheme and presence of comorbidities do present a statistically significant association (p value<0.01).